Some Fallacies in the Interpretation of Social Costs - Graham, Frank D. (Quarterly Journal of Economics, 1925)
Some Fallacies in the Interpretation of Social Costs: A Reply Get access Frank D. Graham Frank D. Graham Princeton University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 39, Issue 2, February 1925, Pages 324–330, https://doi.org/10.2307/1884879 Published: 01 February 1925